Translational Strategy of Pattern Title of Phra Somdej into Chinese in Emperor of Amulets: The strategies and the translational problems of pattern titles of Phra Somdej to Chinese in The Emperor of amulets - เขาวงค์ เฟื่องฟ้า (Chinese Language and Culture Journal, 2021)
The objective of this research was to study the translational strategy of pattern title of Thai amulets into Chinese language. Information originated from instruction book of Emperor of Amulet (Chinese edition) is study course of Phra Somdej (Toh Brahmaransi)《佛牌之王阿赞多崇迪佛研究课程教课用书》including 3 families and 18 pattern titles of Phra Somdej. Data displayed as the most hierarchy commonly used translation strategies with percentages in parenthesis is Rendition (22.2%), followed by Deletion (11.11%), Transcription (11.11%), Substitution (5.55%), Conventionality (5.55%), and Transposition (5.55%), respectively. In addition, we surveyed how translators used each type of translation strategy (For example, how do translators do Deletion procedure? How do translators delete any contexts?) Based on information obtained from this research, the results show that the most mistake was the incorrect pattern title, which was 38.88%. Therefore, we examined causes and problems found in translation. The results demonstrate that translators have tended to stick to the exact translations of the words that appear in the original edition. Also, translators have lacked in either correct word or sentence structure selection. According to occurring problems, we propose an alternative approach for correct and appropriate translation. The results of this research will be useful in improving the quality of translation from Thai to Chinese in the future. Keywords: translation strategies, translation, Phra Somdej